Correction: Receiving, or ‘Adopting’, Donated Embryos to Have Children: Parents Narrate and Draw Kinship Boundaries - Fiona Tasker; Alessio Gubello; Victoria Clarke; Naomi Moller; Michal Nahman; Rachel Willcox (Genealogy)
The authors wish to make the following corrections to this paper published in Genealogy (Tasker et al., 2018), reflecting regrettable misrepresentation of one research participant’s experience [...]